The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/ardp.201700169
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Engineering of Tetracyclic 2,3‐Dihydro‐1H‐benzo[2,3]‐benzofuro[4,5‐e][1,3]oxazine Derivatives: Evaluation for Potential Anticancer Agents

Abstract: Water-mediated one-pot Mannich type condensation of dibenzo[b,d]furan-2-ol with different amines resulted in a large library of novel 2,3-dihydro-1H-benzo[2,3]benzofuro[4,5-e][1,3]oxazine derivatives in moderate to excellent yields. The ortho-aminomethylation of the dibenzofuranols proceeded smoothly in the presence of various aromatic/aliphatic amines and paraformaldehyde, followed by cyclization. All the newly synthesized tetracyclic 2,3-dihydro-1H-benzo[2,3]benzofuro[4,5-e][1,3]oxazine derivatives were chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…[119] The members of a library of over thirty oxazines 101 (Figure 12), that were obtained through the Mannich reaction of dibenzo[b,d]furan-2ol with aromatic and aliphatic primary amines, exhibited broad antiproliferative activity against A549, SK-OV-3 and MCF-7 cancer cell lines that varied from good to poor. [120] The most potent compounds in this library were those with R = n-C 3 H 7 (IC 50 = 11 μM for A549 cells, IC 50 = 17.5 μM for MCF-7 cells) and R = 2,4,5-F 3 C 6 H 2 CH 2 (IC 50 = 7.5 μM for SK-OV-3 cells). Mannich reaction of ten phenolic substrates with ferrocenemethylamines as amine reagents afforded oxazines 102 (Figure 12), but only a few candidates having a basic substituent (R 1 = CH 2 N(CH 3 ) 2 ) on the ferrocene showed moderate cytotoxicity (IC 50 between 11.0 and 31.0 μM) against the hormone-independent, triple-negative breast cancer cell line HCC70.…”
Section: Chemmedchemmentioning
confidence: 95%
See 1 more Smart Citation
“…[119] The members of a library of over thirty oxazines 101 (Figure 12), that were obtained through the Mannich reaction of dibenzo[b,d]furan-2ol with aromatic and aliphatic primary amines, exhibited broad antiproliferative activity against A549, SK-OV-3 and MCF-7 cancer cell lines that varied from good to poor. [120] The most potent compounds in this library were those with R = n-C 3 H 7 (IC 50 = 11 μM for A549 cells, IC 50 = 17.5 μM for MCF-7 cells) and R = 2,4,5-F 3 C 6 H 2 CH 2 (IC 50 = 7.5 μM for SK-OV-3 cells). Mannich reaction of ten phenolic substrates with ferrocenemethylamines as amine reagents afforded oxazines 102 (Figure 12), but only a few candidates having a basic substituent (R 1 = CH 2 N(CH 3 ) 2 ) on the ferrocene showed moderate cytotoxicity (IC 50 between 11.0 and 31.0 μM) against the hormone-independent, triple-negative breast cancer cell line HCC70.…”
Section: Chemmedchemmentioning
confidence: 95%
“…Aminomethylation of phenoxodiol with benzylamine under particular reaction conditions afforded bis‐oxazine 100 , whose anticancer activity was comparable to that of the related benzyl‐substituted mono‐oxazine 98 (IC 50 =5.3 μM for MDA‐MB‐231 cells and IC 50 =5.7 μM for SHEP cells) [119] . The members of a library of over thirty oxazines 101 (Figure 12), that were obtained through the Mannich reaction of dibenzo[ b , d ]furan‐2‐ol with aromatic and aliphatic primary amines, exhibited broad antiproliferative activity against A549, SK‐OV‐3 and MCF‐7 cancer cell lines that varied from good to poor [120] . The most potent compounds in this library were those with R= n ‐C 3 H 7 (IC 50 =11 μM for A549 cells, IC 50 =17.5 μM for MCF‐7 cells) and R=2,4,5‐F 3 C 6 H 2 CH 2 (IC 50 =7.5 μM for SK‐OV‐3 cells).…”
Section: Anticancer and Cytotoxic Activity Of Mannich Bases Derived F...mentioning
confidence: 99%
“…Also, compounds 30 to 36 (Figure 7) showed moderate activity against lung cancer cell line with IC 50 values ranging from 11 to 15.9 μM. SAR studies indicated that N‐alkyl substituted compounds have higher affinity for biological activity than aromatic substituent [30] …”
Section: Biological Activities Of 13‐oxazine Derivativesmentioning
confidence: 99%
“…SAR studies indicated that N-alkyl substituted compounds have higher affinity for biological activity than aromatic substituent. [30] Kakkerla et al reported the synthesis of 3,4-dihydro-8-methoxy-3-(3-methylisoxazol-5-yl)-2H-benzo[e] [1,3]oxazine derivatives in 2017 using 5-amino-3-methylisoxazole which was treated with different salicylaldehydes in methanol and refluxing to give desired derivatives. The synthesized derivatives were evaluated for in vitro cytotoxicity against three different human cancer cell lines HeLa, MCF-7 and A549 taking cisplatin as reference drug.…”
Section: Anticancer Activity Of 13-oxazine Derivativesmentioning
confidence: 99%
“…On the other hand, 1,3‐thiazine derivatives, an important class of heterocyclic compounds, have a wide range of biological properties[ 66 , 67 ] including antiproliferative,[ 68 , 69 , 70 , 71 , 72 ] analgesic, [73] anticonvulsant,[ 74 , 75 ] anti‐inflammatory, [76] antibiotic, [77] antimicrobial,[ 75 , 78 , 79 , 80 ] antimalarial, [81] and antihypertensive [82] properties. A literature survey revealed that also 1,3‐oxazine moieties exhibit a broad range of pharmacological activities,[ 83 , 84 ] such as anticancer,[ 85 , 86 , 87 , 88 , 89 ] antimicrobial[ 90 , 91 ] and anti‐inflammatory[ 92 , 93 ] effects, which showed their potential value in developing new therapeutic agents.…”
Section: Introductionmentioning
confidence: 99%